1997
DOI: 10.1038/nsb1297-1039
|View full text |Cite
|
Sign up to set email alerts
|

A designed four helix bundle protein with native-like structure

Abstract: A 108 amino acid protein was designed and constructed from a reduced alphabet of seven amino acids. The 2.9 A resolution X-ray crystal structure confirms that the protein is a four helix bundle, as it was designed to be. Hydrogen/deuterium exchange experiments reveal buried amide protons with protection factors in excess of 1 x 10(6) in the range characteristic of well protected protons in functional folded proteins (10(3)-10(8)) rather than protons in rapid exchange (0-10(2)). The protein is monomeric at 1 mM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
99
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(100 citation statements)
references
References 34 publications
1
99
0
Order By: Relevance
“…31,36,[42][43][44] Conversely, four helix bundles are a common structural motif in both natural and designed proteins. 16,25,45 For this reason, we will focus the rest of our analysis on A16-based systems (systems with four-helix bundles as native-like structures). The B16-based systems (systems with four-b-strand bundles as native-like structures) will be considered as an essential benchmark set of systems for extending the validity of our model to both a helix and b strand folds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…31,36,[42][43][44] Conversely, four helix bundles are a common structural motif in both natural and designed proteins. 16,25,45 For this reason, we will focus the rest of our analysis on A16-based systems (systems with four-helix bundles as native-like structures). The B16-based systems (systems with four-b-strand bundles as native-like structures) will be considered as an essential benchmark set of systems for extending the validity of our model to both a helix and b strand folds.…”
Section: Resultsmentioning
confidence: 99%
“…Several experimental studies have shown that it is possible to design four-helix bundle proteins with native-like properties considering principally the intrinsic propensities and the pattern of polar and non polar amino acids. [16][17][18][19][20][21] It is worth noting that all these protein design studies relied also on the rational choice of specific interresidue contacts (to optimize the packing within the hydrophobic core) as well as on the explicit definition of the turn regions. A more general, combinatorial approach to de novo protein design was introduced by Hecht and coworkers who synthesized several four-helix bundle proteins, with native-like properties, using sequences composed from a set of amino acids with high helical propensities and with fold-appropriate patterning.…”
Section: Introductionmentioning
confidence: 99%
“…Examples include peptides of approximately 25 residues patterned after the zinc finger motif. [47][48][49][50][51] Further, approximately 20-residue peptides that adopt marginally stable antiparallel β-sheets have been described, [52][53][54][55][56] and native-like two-helix, 57 three-helix, 13 and four-helix 58,59 bundles have been designed and structurally characterized. Here we describe a family of dimeric four-helix bundles with properties ranging from highly mobile molten globules to fully native-like folds.…”
Section: Conformational Specificitymentioning
confidence: 99%
“…In contrast, the antiparallel coiled coils, for which rational design principles have only recently been specified (20)(21)(22)(23)(24)(25)(26), are less structurally scrutinized (15,(27)(28)(29)(30). Both configurations play critical roles in biology, acting for example as oligomerization domains, sites of protein/protein recognition, and nucleic acid binding elements (31-33).…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%